The Renaissance computer : knowledge technology in the first age of print - Rhodes, Neil, 1953-; Sawday, Jonathan (Routledge, 2000)
Some of today's foremost Renaissance scholars look afresh at the remarkable products of the first age of print and explore how these anticipated many of the conditions of the present digital age.